2016
DOI: 10.5194/tc-10-1297-2016
|View full text |Cite
|
Sign up to set email alerts
|

Development and calibration of an automatic spectral albedometer to estimate near-surface snow SSA time series

Abstract: Abstract. Spectral albedo of the snow surface in the visible/near-infrared range has been measured for 3 years by an automatic spectral radiometer installed at Dome C (75 • S, 123 • E) in Antarctica in order to retrieve the specific surface area (SSA) of superficial snow. This study focuses on the uncertainties of the SSA retrieval due to instrumental and data processing limitations. We find that when the solar zenith angle is high, the main source of uncertainties is the imperfect angular response of the ligh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(140 citation statements)
references
References 65 publications
2
128
0
Order By: Relevance
“…In addition to the instrumental errors, the surface slope at the footprint scale may influence the retrieval results. Using data from Picard et al (2016), Dumont et al (2017) found variations of the surface slope caused by wind drift at Dome C of ±2 • . They estimated a resulting uncertainty of 10 % in retrieved SSA due to these variations of the surface slope.…”
Section: Retrieval Of Optical Snow Grain Size From Spectral Albedo Mementioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the instrumental errors, the surface slope at the footprint scale may influence the retrieval results. Using data from Picard et al (2016), Dumont et al (2017) found variations of the surface slope caused by wind drift at Dome C of ±2 • . They estimated a resulting uncertainty of 10 % in retrieved SSA due to these variations of the surface slope.…”
Section: Retrieval Of Optical Snow Grain Size From Spectral Albedo Mementioning
confidence: 99%
“…Picard et al (2016) estimated that a hypothetical change in global surface albedo of 1 % would offset a difference in reflected energy comparable to the globally averaged radiative forcing of 1.82 W m −2 caused by the increase in CO 2 concentration since the preindustrial time (Myhre et al, 2013). This change in global surface albedo could be caused either by a variation in snow and sea ice cover or by a change of the snow albedo itself.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the summer 2013/14, regular sampling of surface (0 to 3 cm) and sub-surface (3 to 6 cm) snow were carried out at Dome C. Once a day, two samples of snow at each level were taken along with specific surface area (SSA) measurements to 25 evaluate the size of the grains and therefore, how much metamorphism has taken place (Picard et al, 2016b). These data are presented in Fig.…”
Section: Surface and Sub-surface Snow Isotopic Exchangesmentioning
confidence: 99%
“…There are no measurements of SSA recorded during 2009-2010 for skin layer snow. The SSA and effective grain radius in this study are estimated based on observations at Dome C from 2012 to 2015 by Picard et al (2016) as well as the annual temperature variation, as shown in Fig. B4.…”
Section: Other Model Inputsmentioning
confidence: 99%